Analisis Kekeliruan Judex Factie Menilai Keterangan Saksi Sebagai Saksi Testimonium De Auditu Yang Menjadi Dasar Pengajuan Kasasi Oleh Penuntut Umum - Aninda Diah Rahmawati; Sri Wahyuningsih Yulianti, S,H., M.H (Sebelas Maret University, 2017)
Case reviewed in Supreme Court Verdict Number : 493 K/Pid/2014 constitute case of persecution conducted colletively by the Defendant I and Defendant II. Public Prosecutor filed an appeal by excuse of Judex Factie are not implement or not implemented laws properly and Council of Bulukumba District Court Judges does not consider facts and circumstances, as well as evidence obtained from the examination in court regarding statements of witness by Irwan considered as a wittness Testimonials de Auditu. Results of research that Public Prosecutor an appeal excuse in accordance with Article 253 of Criminal Procedure Code. Judex Factie are not implemented the law properly. Judex Factie mistakenly in assessment statements of witness by Irwan as a wittness Testimonials de Auditu. Consideration of Supreme Court judges cancelled the verdict because Judex Factie considers mistakenly implemented the law to conduct incorrect assessment on statements the witness by Irwan. Supreme Court cancelled the Verdict of Bulukumba District Court Number : 84/Pid.B/2013/PN.BLK and prosecute themselves in Verdict Number : 493 K/Pid/2014. Supreme Court considered that the witness statements by Irwan are lawful according to Criminal Procedure Code, and Supreme Court decided that Defendant I convicted legally and convincingly to persecution collectively according to the indictment of Public Prosecutor Article 351 Paragraph (1) in conjunction with Article 55 Paragraph (1) of Criminal Code first book. Keyword : Cassation, Testimonials de Auditu, Persecution Collectively